Srečko Kosovel 1926–2026: Pregled prevedenih del ob 100. obletnici smrti (University of Maribor Press, 2025)
Srečko Kosovel (1926–2026) - A Review of Translated Works on the Occasion of the 100th Anniversary of His Death. The monograph Srečko Kosovel (1926–2026) - a review of translated works on the occasion of the 100th anniversary of his death brings together the poet’s translation opus in 12 foreign languages in one place. The monograph consists of an introduction and a set of contributions by authors who examine the poet’s translation opus in 12 foreign languages. In the contributions, the authors present a set of translated works, which is more extensive in some languages, e.g. in Italian, and therefore in the monograph several contributions that discuss the poet’s opus in this language are included. The authors continue with the poet’s reception in a foreign country, dedicate a few words to the translators, and then present the translation characteristics of the collections in individual poems. The authors examine the characteristics of translation by individual periods, present various poems and the characteristics of translations, either in individual time periods or in terms of translation by one or more translators. The work offers an insight into a comprehensive range of translated works, which are then presented and discussed, and offers the possibility of future upgrades and improvements.